Prevalence of high-risk for obstructive sleep apnea in attention deficit hyperactivity disorder children referred to psychiatry clinic and impact on quality of life - Prajsuchanai, Tipkamol; Tanphaichitr, Archwin; Hosiri, Tikumporn; Ungkanont, Kitirat; Banhiran, Wish; Vathanophas, Vannipa; Gozal, David (Frontiers in Psychiatry, 2022)
Objectives: To study the prevalence of high-risk obstructive sleep apnea (OSA) in attention deficit hyperactivity disorder (ADHD) children in a child and adolescent psychiatry clinic using the Thai version of the Pediatric Obstructive Sleep Apnea Screening Tool (POSAST) questionnaire. The secondary objective was to evaluate the quality of life and identify associated factors for high-risk OSA in ADHD children. Study design: Prospective cross-sectional study Material and method: Caregivers of pediatric patients aged 5-18 years old and diagnosed with ADHD by child and adolescent psychiatrists were surveyed about their child's sleeping habits. Results: Two hundred and seventy-four subjects were included. The patients’ mean age was 10.4 ± 2.6 years, and 82.8% were males. There were 30 children (10.9%) diagnosed with obesity, 46 (16.8%) with chronic rhinitis, and 9 (3.3%) with asthma. The median duration of ADHD symptoms was 22.1 months. The prevalence of high-risk OSA was 18.2% and was associated with significantly reduced quality of life (adjusted OR = 4.46, 95% CI: 2.26-8.81, P < 0.001). A significant association between high-risk OSA and obesity also emerged (adjusted OR = 2.84, 95% CI: 1.17-6.88, P = 0.021). Conclusion: An elevated prevalence of high-risk OSA is present among Thai children with ADHD, and significantly impacts quality of life. A significant association between high-risk OSA and obesity is also detected in patients with ADHD. Therefore, screening for high-risk OSA in ADHD patients may likely facilitate early detection and treatment of OSA, and potentially prevent adverse consequences.